Muestra ideal para la predicción de la relación diámetro - altura total en el crecimiento de las plantas de Guarea macrophylla M. Vahl. En bosque natural. Puerto Almendra, Loreto, Perú - 2021 - García Torres, Wendy Lessy (2022)
The research was carried out at the Faculty of Forest Sciences - UNAP, in San Juan Bautista, Maynas, Loreto. Its objective was to obtain the optimal sample for the prediction of the diameter-total height relationship in Guarea macrophylla M. Vahl plants. in different samples in natural forest. The diameter and total height data of the trees of the species under study with DAP ? 10 cm were used; the samples were, Sample 1 (M1) with 30 individuals distributed in diameter classes; Sample 2 (M2) = 30 randomly chosen data and Sample 3 (M3) = Representative sample (66 data). The results of the diameter - total height relationship indicate that the allometric power model was the one with the best fit and the degree of relationship was excellent; The equations for the prediction of the diameter-total height relationship are: Sample 1: Y = 1.940 + (t 0,664); Sample 2: Y = 1.626 + (t 0,701); Representative Sample: Y = 1.717 + (t 0,687).